2021
DOI: 10.1097/wad.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Care and Unmet Needs of Individuals With Dementia With Lewy Bodies and Caregivers

Abstract: Background: Patient-centered care requires understanding patient preferences and needs, but research on the clinical care preferences of individuals living with dementia and caregivers is sparse, particularly in dementia with Lewy bodies (DLB). Methods: Investigators conducted telephone interviews with individuals living with DLB and caregivers from a Lewy body dementia specialty center. Interviews employed a semistructured questionnaire querying helpfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…However, psychiatric symptoms were the most frequently selected symptom domain for the symptom that causes the caregiver most distress. This result supports the results of a previous study that found that BPSD is the most burdensome DLB symptom for caregivers [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, psychiatric symptoms were the most frequently selected symptom domain for the symptom that causes the caregiver most distress. This result supports the results of a previous study that found that BPSD is the most burdensome DLB symptom for caregivers [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on these previous studies, BPSD and ADL impairments, which are associated with high caregiver burden, may be considered as caregivers’ treatment needs, but the treatment needs of the patients themselves cannot be known from these studies. Few studies have investigated the unmet needs of both patients with DLB and their caregivers [ 19 , 20 ]. In one study [ 19 ], BPSD and ADL impairments were considered as treatment needs of caregivers due to the high caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable progress could be made in the care of LBD through improved utilization of existing resources (eg, the Lewy Body Dementia: Information for Patients, Families, and Professionals freely available booklet from the National Institutes on Health) 18. Barriers to such utilization, including awareness, limited time with clinicians, confusing or inconsistent terminology, and insurance coverage, must be identified and eliminated 19…”
Section: Discussionmentioning
confidence: 99%
“…18 Barriers to such utilization, including awareness, limited time with clinicians, confusing or inconsistent terminology, and insurance coverage, must be identified and eliminated. 19 Caregiving Research in LBD Given the reliance of the US healthcare system on informal caregivers for chronic disabling conditions, focused research on caregiving in LBD is essential. 5,10 The voices of LBD caregivers should be elevated within research planning and execution, leveraging their expertise and direct knowledge of the disease.…”
Section: Burden Of Lbd Symptomsmentioning
confidence: 99%